Logística reversa, reutilização e trabalho social na moda (ModaPalavra e-periódico, 2014)
The clothing product developed according to the fashion system has a short life cycle. From raw material to disposal, the environmental impacts generated by the fashion products have been studied to minimize the consequences for the environment. This study discusses the final step, post use, applying the concept of reverse logistics, which is the return of the products to companies for new utilization, and reuse of discarded pieces serving as raw material in social enterprises. The reuse of discarded pieces of clothing as raw material for the development new products contributes to the reduction of environmental and social impacts.
Keywords: fashion; sustainability; reverse logistics